The role of enamelysin (mmp-20) in tooth development: systematic review - Cuellar-Rivas, Estefanía; Pustovrh-Ramos, María Carolina (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: ameloblasts are cells responsible for the production and mineralization of the organic matrix of enamel through several stages: pre-secretory, secretory, transition, and maturation. The organic matrix components are produced in the secretory phase. In the maturation phase, the organic component is removed and the mineralization process starts. This process requires the involvement of matrix metalloproteinase 20 (MMP-20), also called enamelysin. Several studies have shown the presence of MMP-20 in tooth development and its relationship to alterations in enamel formation. The objective was: to classify the different studies and laboratory techniques used to demonstrate the involvement of enamelysin in tooth development and its relation to pathologies during enamel formation. Methods: a systematic review was conducted with the following bibliographic databases: PubMed, Science-Direct, Hinari, and SciELO, in order to classify the different studies related to the involvement of MMP-20 in tooth development and the methods to detect its expression, between the years of 2009 and 2014. Results and conclusions: in vitro models show that MMP-20 has specific cleavage sites for enamel matrix proteins. This process is altered by chemical composition, ions, and the presence of hydroxyapatite. Enamel morphology is altered in the knockout models. In human studies, MMP-20 has been associated with increased susceptibility to dental caries, enamel thickness, and dental agenesis.